2015
DOI: 10.1017/neu.2015.9
|View full text |Cite
|
Sign up to set email alerts
|

Levels of functional disability in elderly people in Tanzania with dementia, stroke and Parkinson’s disease

Abstract: Levels of disability from these conditions is high and is likely to increase with demographic ageing. Innovative, community-based strategies to reduce disability levels should be investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 31 publications
1
14
0
1
Order By: Relevance
“…As populations age, dementia is becoming increasingly common and is associated with high levels of disability (Prince et al, 2011a;Dotchin et al, 2015;Kisoli et al, 2015). Despite the growing body of epidemiological data, diagnosis of dementia in many parts of SSA can be difficult because of a shortage of specialist physicians (Bower and Zenebe, 2005;Dotchin et al, 2013) and a lack of appropriate screening tools.…”
Section: Introductionmentioning
confidence: 99%
“…As populations age, dementia is becoming increasingly common and is associated with high levels of disability (Prince et al, 2011a;Dotchin et al, 2015;Kisoli et al, 2015). Despite the growing body of epidemiological data, diagnosis of dementia in many parts of SSA can be difficult because of a shortage of specialist physicians (Bower and Zenebe, 2005;Dotchin et al, 2013) and a lack of appropriate screening tools.…”
Section: Introductionmentioning
confidence: 99%
“…In regression modelling, initial post-stroke disability appears to be a more important predictor of case-fatality at 7 years than age and gender. The high prevalence of functional disability in stroke survivors living in Tanzania has been noted previously (19).…”
Section: Discussionmentioning
confidence: 80%
“…To simplify the model interpretation, for the purposes of the Cox regression model, age at stroke data were used untransformed and uncategorized and Barthel index scores were dichotomized into severe disability (score 0-14) and no, moderate or mild disability (score [15][16][17][18][19][20].…”
Section: Methodsmentioning
confidence: 99%
“…Kisoli et al 27 assessed disability among an elderly population with various neurological diseases using the Barthel Index and found that 63% of CVA survivors were dependent for basic activities of daily living. It can be seen that there is a large discrepancy in the prevalence of disability and many factors can influence such rates, such as the sample location, age of participants, the recurrence of CVAs, the time of evaluation and the type of instrument applied.…”
Section: Discussionmentioning
confidence: 99%